Dominansi Bintang Laut (Asteroidea) di Pantai Awang Kabupaten Lombok Tengah - Khairunnisah, Khairunnisah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
This study aims to determine the dominance of sea stars (Asteroidea) at Awang Beach, Central Lombok Regency. The research type is descriptive comparative. Sampling was conducted at three stations: Station I, Station II, and Station III, using the transect-quadrat method. Data collection techniques included direct observation and documentation. The parameter measured was sea star dominance. The results indicate that the sea star dominance index at the three stations is 0.576, categorized as low.